Bone versus implant: an atypical presentation of a typical complication of forearm fractures - Vatsya, Pulak; Gupta, Anupam; Mittal, Samarth; Trikha, Vivek (International Journal of Research in Orthopaedics, 2021)
Both bone forearm fractures are one of the most common upper limb fractures operated by orthopedicians. Although the primary surgery is usually relatively straight forward and simple, but we present a case where the primary surgery failed and the patient presented with a deformed hand after 5 months, even though there were signs of union on radiographs. When operated upon, although the ulna had undergone primary bone healing and a peri-implant fracture had occurred, whereas radius had refractured from the fracture site and the plate was bent giving the deformed appearance. We discuss this unique complication, the planning, difficulties and scope of errors in such a situation, where the race to union is won by ulna but lost by radius.